Scale Issues in Soil Hydrology - Vogel, H-J. (2020)
Soil hydrology is a key control for the functioning of the terrestrial environment. Many environmental issues that we need to tackle today are directly linked to soil water dynamics. This includes agricultural production and food security, nutrient cycling and carbon storage, prevention of soil degradation and erosion, and last but not least, clean water resources and flood protection. However, these problems need to be addressed at the scales of fields, regions, and landscapes, while soil water dynamics and soil hydraulic properties are well understood and typically measured at much smaller scales—the comfort zone of soil physics. An obvious problem is how to link these vastly different scales and how to profit from small‐scale understanding to improve our capability to predict what is going on at the large scale. In this update, this problem is discussed based on insights gained during the last decades. As a synthesis, a two‐step scaling approach is proposed for modeling soil water dynamics from local to landscape scales where the scale of the soil profile is the stepping stone.